Hubungan Antara Terpaan Promosi Penjualan dan Tingkat Kepercayaan dengan Minat Beli di Situs Belanja Online Lazada - Iva Devi, Marita; Widowati Herieningsih, Sri (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
The development of technology and information is growing rapidly and it has an impact on business people to develop their company into an online business. The existence of sales promotion and consumer trust factors become the basis for forming consumer purchase intention. The purpose of this study was to determine the relationship between exposure to sales promotions and the level of trust with purchase intention in Lazada's online shopping site. In determining the hypothesis to be used, this study uses behavioral learning theory and planned behavior theory. The study population was women aged 15-34 years in Semarang City who were exposed to Lazada sales promotion exposure and within the last 1 month had not made a transaction at Lazada. Hypothesis test results (H1) obtained a significance value of 0.001 and a correlation coefficient of 0.352. While the results of hypothesis testing (H2) obtained a significance value of 0.000 and a correlation coefficient of 0.442. From the results of these studies, it is recommended to increase consumer purchase intention to combine sales promotions with advertisements.